The effect of topical endometrial scratching on pregnancy outcome in women with previous failure of intrauterine insemination: A non-randomized clinical trial - Farahnaz Farzaneh; Farzaneh Khastehfekr (Shahid Sadoughi University of Medical Sciences, 2021)
Background: The prevalence of infertility is increasing worldwide and the treatment is one of the important issues. Objective: This study aimed to evaluate the effect of local endometrial scratching on pregnancy outcomes in women with previous failure of intrauterine insemination. Materials and Methods: This non-randomized clinical trial study was performed on 336 women referred to the infertility clinic of Ali ebn-e Abitaleb Hospital of Zahedan (between May and November 2019). Women were divided into two groups: endometrial scratch as case and a control group. In the case group (n = 173), endometrial scratching was performed on days 8-9 of the menstrual cycle in addition to routine infertility treatments, while in the control group (n = 163), only routine treatment was performed. Chi-square test was used to compare the frequency of male factor severity and the percentage of successful pregnancies between both groups and was used to investigate the effect of male factor on the fertility rate in each group (moderate male factor and mild male factor). Results: The mean age of the women was 28.4 ± 5.2 yr. The success rate of pregnancy in the case group was 12.3% and in the control group 11%, which were not statistically significant (p = 0.697). Conclusion: Overall, the results of this study showed that endometrial scratching had no effect on the pregnancy rate.